2011
DOI: 10.1080/00071668.2011.590795
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolutionary analysis of the duck MYOD gene family and its differential expression pattern in breast muscle development

Abstract: 1. The objective of the research was to investigate the molecular evolutionary relationships between the duck myogenic determination factors (MYOD) gene family members and their roles in muscle development. 2. The four members of the duck MYOD gene family were cloned using RT-PCR, and their relative mRNA expression during duck muscle development was measured using qRT-PCR. 3. The results showed that MyoD and Myf5 clustered together, as did MyoG and MRF4 based on their complete amino acid sequence and the basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…The present result also showed that MRFs expression had been slightly detected in other tissues of grass carp, i.e., heart, hepatopancreas, intestine, kidney. Although previous reports that MRFs were only expressed in skeletal muscle (Sabourin and Rudnicki 2000;Rescan 2001;Gregory et al, 2004;Kobiyama et al, 1998;Du et al, 2003), it was in accordance with the following findings that MRFs expression had been detected in 14-day duck embryo myocardium (Liu et al, 2011) and in other non skeletal muscel of flounder (Paralichthys olivaceus), i.e., heart muscle, spleen, kidney, gill, eye (Zhang et al, 2010). MRFs expression levels in these non skeletal tissues was about 1%-5% of the expression in muscle (Zhang et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The present result also showed that MRFs expression had been slightly detected in other tissues of grass carp, i.e., heart, hepatopancreas, intestine, kidney. Although previous reports that MRFs were only expressed in skeletal muscle (Sabourin and Rudnicki 2000;Rescan 2001;Gregory et al, 2004;Kobiyama et al, 1998;Du et al, 2003), it was in accordance with the following findings that MRFs expression had been detected in 14-day duck embryo myocardium (Liu et al, 2011) and in other non skeletal muscel of flounder (Paralichthys olivaceus), i.e., heart muscle, spleen, kidney, gill, eye (Zhang et al, 2010). MRFs expression levels in these non skeletal tissues was about 1%-5% of the expression in muscle (Zhang et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…MRFs expression was shown to be in a sequentialmanner during myogenesis in mice and zebrafish (Hinits et al, 2009;Roy et al, 2002;Jin et al, 2007). Simultaneously the expression patterns of MRFs had been reported to be different in different manmals (Sabourin and Rudnicki 2000), cat fish (Gregory et al, 2004) and in many other animals, i.e., duck, channel catfish, carp, gilthead seabream, zebrafish and flounder (Paralichthys olivaceus) (Liu et al, 2011;Rescan 2001;Kobiyama et al, 1998;Du et al, 2003;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore higher expression patterns of MYOD in BM suggesting its involvement to maintain the development of different muscles. These findings also agreed with the study of Liu et al, (2011). In the pectoral muscle of Pekin duck, fastest muscle development identified on 19 or 20 d in embryonic period (Gu et al, 2013) by the expression of MRF4 and MYOG genes.…”
Section: Effect Of Myogenic Regulatory Factors (Mrfs) In Myogenesissupporting
confidence: 80%
“…Thus far, many candidate genes and gene families responsible for growth traits have been identified in duck; these include myogenic regulatory factor (MRF) family members [myogenic factor 5 (MYF5), muscle-specific regulatory factor 4 (MRF4), myoblast determination protein (MYOD), and myogenin (MYOG) 3 ], myocyte enhancer factor-2 gene family (MEF2) 4 , lipoprotein lipase (LPL) 5 , and insulin-like growth factors (IGFs) 6 . Several pathways regulating lipid deposition, including proliferator-activated receptor-gamma (PPARγ), mitogen-activated protein kinase (MAPK), Wnt, Hedgehog, and CCAAT/enhancer bindings protein α (C/EBPα) signalling pathways, have also been reported 7, 8 .…”
Section: Introductionmentioning
confidence: 99%